THE EFFECT OF FRAUD DIAMOND DIMENSIONS AND ACADEMIC PROCRASTINATION ON STUDENT ACADEMIC CHEATING BEHAVIOR - Andrea Sifana; Khresna Bayu Sangka (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2025)
This research aims to determine the influence of diamond fraud dimensions and academic procrastination on academic cheating behavior among students in the Economic Education FKIP UNS undergraduate study program. This research is descriptive quantitative research. The data source for this research comes from primary data from respondents, namely students of the 2020-2023 FKIP UNS Bachelor of Economics Education Study Program. The sampling technique was carried out using simple random sampling. Data collection was carried out by distributing questionnaires containing questions. The validity test was carried out using the Pearson correlation product moment technique. Reliability testing was carried out using the Cronbach's Alpha formula. Data analysis was carried out using descriptive statistical analysis and statistical analysis including prerequisite tests, partial t tests, and coefficient of determination. The results of this research are that the variables of opportunity and ability have a significant effect on academic cheating behavior. While the variables of pressure, rationalization, and academic procrastination do not have a significant effect on academic cheating behavior. Key words: Pressure, opportunity, rationalization, ability, academic procrastination, and academic cheating.